Pelatihan Sistem Informasi Pengelolaan Layanan dan Manajemen Pelanggan untuk Optimalisasi Layanan pada Era Digital - I Gede Iwan Sudipa; Komang Kurniawan Widiartha; I Komang Arya Ganda Wiguna; Bagus Kusuma Wijaya; Gustiadi Gustiadi; Achmad Selamat Fauzi (FKIP, Universitas Palangka Raya, 2023)
In the digital era, the role of information technology in facilitating services has presented both challenges and opportunities for businesses seeking to provide exceptional customer service. To remain competitive and maintain customer satisfaction, businesses need to implement technology in the form of service management and customer management information systems. Using technology, community service endeavors aim to establish a service management information system and consumer management. For employees and clients, assistance is provided through technology transfer, socialization, training, and technical support. The outcomes of this assistance indicate advancements in consumer data management and the implementation of more effective technology. The PKM implementation team at INSTIKI discovered that active participation from partners and customers contributed to the success of the program. Partner participation helps identify actual needs and issues in the use of information systems, enabling mentoring programs to be tailored to user requirements and optimize service quality in the digital era.